Seroprevalence of Brucellosis in Camels and Goats and Community Awareness Towards Its Zoonotic Risk in Selected Districts of Afar Region, Ethiopia - Teshager Dubie; Ahmed Seid; Ashenafi Syoum; Fanuel Bizuayehu Yihunie (Veterinary Medicine International, 2025)
Brucellosis is a highly infectious bacterial zoonotic disease that carries substantial economic and public health implications, especially within pastoral and agropastoral communities in Ethiopia. A cross-sectional study was employed from December 2022 to October 2023 to estimate the seroprevalence of brucellosis among camels and goats and to assess community awareness towards its zoonotic importance in selected districts of Afar, Ethiopia. A total of 528 serum samples were sequentially tested using the Rose Bengal plate test (RBPT) and the competitive enzyme-linked immunosorbent assay (c-ELISA). A questionnaire survey was administered to camel and goat owners to assess community awareness of zoonotic importance of brucellosis. Collected data were entered, coded, and analyzed using SPSS version 27 software. In the current study areas, the overall seroprevalence of camels’ and goats’ brucellosis, based on RBPT as well as c-ELISA, was found to be 3.03% and 2.27% with 95% CI; 0.48–5.53. Moreover, the seroprevalence of brucellosis among the species level was 3.75% (n = 9/240) in camels and 2.43% (n = 7/288) in goats in the study districts. The survey indicated that 85% of the pastoral community in the study areas is unaware of the zoonotic significance of camel and goat brucellosis. Moreover, almost 88% of pastoralists and agropastoralists in the study districts were found to handle abortions and retained placentas with their barehands. The calculated Kappa (κ) statistic was found to be 0.853, indicating an “almost perfect” level of agreement between the RBPT and ELISA serological tests. An increased seroprevalence of camel and goat brucellosis in pastoral communities, along with prevailing animal husbandry practices and raw food consumption habits, suggests that brucellosis could pose a significant public health threat in the study areas. This highlights the need for awareness creation to educate farmers about the disease and promote safer practices, ultimately helping to protect the community from brucellosis.